Upaya Peningkatan Kapasitas Pemipilan Jagung dengan Menggunakan Alat Pemipil Jagung Tenaga Surya di Desa Trimoharjo: Penelitian - Toni Okviyanto; Firduas; Hendradinata; Kurniawan, Asep; Yoga Gibrani, Gilang; Maulidi, Sa’bani (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2025)
This community service program aims to improve the postharvest efficiency of corn farmers in Trimoharjo Village, Semendawai Suku III District, Ogan Komering Ulu Timur Regency, through the application of appropriate technology in the form of a solar-powered maize sheller. The main problems faced by farmers are low productivity due to manual shelling and high operational costs of fossil fuel-based machines. The implementation method adopts an engineering design and participatory approach, including needs assessment, design, fabrication, technical training, field implementation, and evaluation. The results show a 300% increase in work efficiency compared to manual methods, with a shelling capacity of 65 kg per hour and a kernel intactness rate of 90–95%. The 200 Wp solar power system can supply energy for 3–4 hours of operation with a full battery charge time of about 5 hours under optimal sunlight. Additionally, the program successfully enhanced farmers’ knowledge of equipment operation and maintenance while fostering local energy independence. This activity not only provided economic benefits through reduced operational costs but also contributed to achieving the Sustainable Development Goals (SDGs), particularly in clean energy and local economic growth.